THE MASTER'S DEGREE WITH COURSES IN BUSINESS, YESTERDAY, TODAY, AND TOMORROW. - Prickett, A. L. (The Accounting Review, 1958)
Abstract The article presents a study of several business schools offering master's degree in business in the U.S. The Master's degree is sometimes considered as terminal and sometimes as a foundation step toward the doctoral degree. The two objectives are usually well harmonized and actually there need not be too much difference between the requirements. For a long time, it has been recognized that many students of superior ability need financial assistance in order to go to college, and this is particularly true if they continue on beyond the first degree. In general, the schools have been holding scholarships for tuition, fellowships for larger amounts including room and board, assistantships with a little greater flexibility, teaching assistantships, teaching associateships and instructorships for top amounts. Since loans have to be paid back, often with interest, the student is reluctant to take a loan if he can secure the means some other way. The survey shows that as compared with seven years ago, the non-service type of grant is gaining and the requests for loan funds decreasing.